2020
DOI: 10.1177/1078345819897634
|View full text |Cite
|
Sign up to set email alerts
|

Improving Medication Adherence Among Drug-Using HIV-Infected Formerly Incarcerated Individuals: A Pilot Test of Two Interventions

Abstract: Incarcerated individuals in the United States are reportedly four times more likely to be infected with HIV than members of the general population, and a substantial proportion have a history of drug use. Postincarceration, many struggle to maintain their antiretroviral therapy (ART) regimen. This pilot study tested the potential performance of two ART adherence interventions, Project ADHerence Education and Risk Evaluation (ADHERE) and Medication Adherence and Care Engagement (MACE) among drug-using HIV-infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…We discovered that a history of imprisonment increases the risk of non-adherence in HIV patients. According to the literature, many HIV-infected prisoners discontinue their viral therapy after they are released [24,25]. Moreover, Baillargeon et al reported that more than 90% of HIV-infected prisoners did not receive ART or stopped their treatment sometime after their release.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…We discovered that a history of imprisonment increases the risk of non-adherence in HIV patients. According to the literature, many HIV-infected prisoners discontinue their viral therapy after they are released [24,25]. Moreover, Baillargeon et al reported that more than 90% of HIV-infected prisoners did not receive ART or stopped their treatment sometime after their release.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…Therefore, less intensive services may be sufficient to initiate HIV care engagement for PWH under community supervision who have been aware of their HIV status for a longer length of time. Another study conducted with a slightly different population (individuals in the community with recent carceral contact [past 5 years]) lends additional support for the implementation of less intensive HIV care–related interventions [ 88 ]. Future research should examine whether there are differences in the types of supports necessary (including brief interventions) to engage PWH with current or recent carceral contact in care relative to the length of time they are knowingly living with HIV, and the length of time since they have been released from detention.…”
Section: Hiv Care Outcomes For Adults Under Carceral Supervision In T...mentioning
confidence: 99%
“…Structural factors such as unstable housing, gaps in health insurance coverage, stigma associated with having HIV, and a history of incarceration may limit the ability of formerly incarcerated individuals to engage in HIV care and maintain optimal ART adherence (Baillargeon et al, 2009; Booker et al, 2013; Dennis et al; 2015; DiPrete et al, 2019; Fu et al, 2013; Haley et al; 2014; Katzen, 2011; Loeliger et al, 2018; Rich et al, 2013; Stephenson et al, 2005; Westergaard et al, 2013). Accessing providers in a timely manner to prevent treatment disruption during their return to the community has been identified as a primary concern among formerly incarcerated PLWH (Loeliger et al, 2018; Rowell-Cunsolo et al, 2020b; Wohl et al, 2011). Additionally, substance use challenges, which are commonly experienced by formerly incarcerated people who use drugs (Chamberlain et al, 2019; Owens et al, 2018), compound and complicate the ability to overcome many of these structural and community-level barriers (Dennis et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Third, we completed a pilot test of the newly designed interventions among a segment of the target population. The current manuscript focuses specifically on components of the multi-component intervention related to substance use and medication adherence; the results for intervention components related to condomless sexual behavior outcomes have been reported elsewhere (Rowell-Cunsolo et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%